Strategi Pola Pengembangan Karir Pegawai dalam Meningkatkan Kinerja Pegawai Kementerian Agama Kabupaten Banyuwangi - Septyyana, Ika Nur (Fakultas Dakwah UIN KHAS Jember, 2023)
Employee career development is a strategic activity in personnel management, aimed at helping employees plan their future careers at their workplace. The research focus in this thesis includes three main questions: (1) strategy for employee career development patterns to improve performance at the Ministry of Religion, Banyuwangi Regency, (2) supporting and inhibiting factors in improving employee performance at this agency. This research aims to understand the strategies, mechanisms and factors that influence employee career development at the Ministry of Religion, Banyuwangi Regency. The method used is descriptive qualitative with data collection techniques through observation, interviews and documentation. Data analysis was carried out by collecting, reducing, presenting and verifying data, as well as SWOT analysis as the main approach. The research results show that career development strategies involve creating disciplinary rules, determining appropriate tasks, providing motivation, and implementing reward and punishment systems. Implementation mechanisms include participation in activities such as official meetings, training, seminars, and various forms of career development activities. Supporting factors include the ability to cooperate between employees and collaborate with related parties, while inhibiting factors involve limited human resources and funds. In a SWOT analysis, strength lies in the ability to collaborate between employees and collaborate with related parties. Weaknesses involve limited human resources and funds. Opportunities are found in training, seminars and technical guidance, as well as providing rewards to employees.